Empirical investigation of the dynamics of students’ will qualities as subjects of the educational process in learning activities - Mambetalina Аliya; Turarova, Gulnaz (Pedagogy and Psychology, 2021)
The article presents the results of an empirical study of the dynamics of the manifestation of volitional qualities of students as subjects of the educational process. The results of the study can complement the content of training courses in the section "Will and volitional qualities" - general psychology: psychology of emotions and will; age-related psychology. In this study, the authors are based on the classification of volitional qualities developed by E.P. Ilyin. The dynamics of the volitional qualities of students as subjects of the educational process in the process of educational activities of the university is determined and described. The authors revealed the level of development of self-willed and moral-volitional qualities in students as subjects of the educational process at the initial stages of education at the university. It has been revealed and statistically confirmed that senior students as subjects of the educational process are characterized by a high level of self-willed qualities and an average level of moral and volitional qualities in educational activities. The content is revealed and the positive dynamics of self-volitional and moral-volitional qualities of students as subjects of the educational process in educational activities is determined